2020
DOI: 10.1108/ijesm-03-2020-0015
|View full text |Cite
|
Sign up to set email alerts
|

Oil-food price dynamics in an oil-dependent emerging economy

Abstract: Purpose This paper aims to examine the transmission from oil price to local food price returns in Nigeria from January 1995 to May 2019. Design/methodology/approach To circumvent erratic behaviours and account for possibilities of noises at the edge of the wavelet signals, the paper combines wavelet and Markov-switching techniques to determine the significance and magnitude of oil–food price dynamics across different time scales. Findings It is shown that oil to food price pass-through changed across frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 27 publications
2
19
0
Order By: Relevance
“…Additionally, numerous studies have found possible asymmetries involving oil and food prices by exploring NARDL, Markov switching, and VAR methodologies. Ibrahim (2015), Meyer, Sanusi, and Hassan (2018), and Adeosun et al (2021) all indicate mixed results regarding food prices' relation to oil prices.…”
Section: Review Of the Related Literaturementioning
confidence: 97%
See 3 more Smart Citations
“…Additionally, numerous studies have found possible asymmetries involving oil and food prices by exploring NARDL, Markov switching, and VAR methodologies. Ibrahim (2015), Meyer, Sanusi, and Hassan (2018), and Adeosun et al (2021) all indicate mixed results regarding food prices' relation to oil prices.…”
Section: Review Of the Related Literaturementioning
confidence: 97%
“…Using a panel vector autoregressive (PVAR) model, Taghizadeh-Hesary et al (2018) examine the relationship between fuel and food prices rigorously and conclude that oil prices have a considerable impact on food rates in designated Asian economies. Recently, Adeosun et al (2021) employed wavelet and Markov-switching techniques to investigate the oil-food price dynamics in Nigeria. Thus, to eliminate contradicting behaviour and adjust for disturbances near the edge of the wavelet impulses, the author used monthly data from 1995: M1 to 2019: M5.…”
Section: Review Of the Related Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Concerning the case of Algeria, numerous studies have investigated the relationship between oil price and exchange rates; however, they have considered only the linear relationship between these variables (Sorsa, 1999; Koranchelian, 2005; Benhabib et al , 2014), while it is well documented in the empirical literature that the path of oil price is asymmetric and volatile (Adeosun et al , 2020). The purpose of this paper is to examine whether changes in oil prices explain the pattern of Algeria real effective exchange rate (REER) using nonlinear nonlinear autoregressive distributed lag (NARDL), frequency domain causality approach and wavelet coherence analysis.…”
Section: Introductionmentioning
confidence: 99%